Diagnostic angiography for identification and management of late vascular injuries in war-related traumatic peripheral vascular injuries: A retrospective cohort study - Efrat Keren Gilat; Boris Khaitovitch; Yiftach Barash; Noam Tau; Eli Konen; Moshe Halak; Daniel Silverberg; Barak Raguan; Vera Sorin; Daniel Raskin (PLoS ONE, 2025)
Purpose One of the feared complications of war-related peripheral vascular injury is the development of delayed hemorrhage. This study describes our experience with an innovative protocol of surveillance diagnostic angiography to detect occult late vascular complications in an effort to prevent delayed hemorrhage. Materials and Methods This retrospective cohort study was conducted at a single level one trauma center, reviewing patients with war-related peripheral vascular injuries caused by penetrating trauma from October 7th, 2023, to January 21st, 2024. Data collected included patient demographics, primary injury characteristics, associated complications, incidence of late vascular injuries (either symptomatic or occult), means of diagnosis, treatment strategies and outcomes. Results The cohort included 41 patients with war-related peripheral vascular injuries affecting 51 limbs. All patients were male (100%) with a median age of 25 years, the majority being soldiers (85%). 24 occurrences of late vascular injuries were observed in 22 (43%) out of 51 limbs (100%). Half were symptomatic, with delayed hemorrhage occurring in 5 limbs in total (10%), and half were asymptomatic. A total of 17 surveillance diagnostic angiographies were performed with the sole indication of identifying occult late vascular injuries in asymptomatic patients, of which 4 (24%) were positive for findings. Five additional diagnostic angiographies were performed to assess late injuries discovered incidentally on imaging studies that were performed for other indications, and all were positive for late vascular injuries. Of all late vascular injuries, a total of 83% required subsequent treatment. Conclusions Late vascular injuries are a potentially lethal complication of war-related peripheral vascular injury. Aggressive surveillance with diagnostic angiography prior to discharge from a high intensity care unit can detect asymptomatic late vascular injuries, the treatment of which may prevent life-threatening hemorrhage.